Pinnularia qinghainensis: a new diatom species (Bacillariophyta) found in the brackish Lake Qinghai, China - Deng, Li-Ying; Blanco, Saúl; Liu, Bing; Quan, Si-Jin; Long, Ji-Yan (Phytotaxa, 2021)
During the investigations of the diatom flora of Lake Qinghai, China (see Liu et al. 2020 for details), specimens of an undescribed species of Pinnularia Ehrenberg (1843: 45) were encountered, which are hereby illustrated and described.